2014
DOI: 10.21206/rbas.v4i2.263
|View full text |Cite
|
Sign up to set email alerts
|

Uso De Caroço De Açaí Triturado Fermentado, Para a Formulação De Substratos Para Produção De Mudas De Quiabo E Tomate

Abstract: O objetivo deste trabalho foi formular substratos, a partir do caroço de açaí triturado fermentado, para produção de mudas de quiabo e tomate. Os experimentos foram conduzidos em delineamento inteiramentecasualizado, e os tratamentos constituídos por cinco substratos (1: 100% de caroço de açaí triturado fermentado; 2: 75% de caroço de açaí triturado fermentado e 25% de substrato comercial Basaplant v/v; 3: 50% de caroçode açaí triturado fermentado e 50% de substrato comercial Basaplant v/v; 4: 25% de caroço de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 0 publications
0
4
1
6
Order By: Relevance
“…Silva et al (2011) and Araújo et al (2017) verified that substrates with organic constituents contributed to increase the number of leaves in Hancornia speciosa and Schizolobium amazonicum seedlings, respectively. Unlike the results presented herein, Erlacher et al (2016) found that the number of leaves of Eruca vesicaria and Brassica oleracea was higher with the use of ground assai pit, if compared to commercial substrate. According to Lima et al (2008), seedlings with a higher leaf production at the time of being taken to the field present a faster initial 1 SH: shoot height (cm); SD: stem diameter (mm); NL: number of leaves; SDM: shoot dry mass (g); RDM: root dry mass (g); TDM: total dry mass (g); DQI: Dickson Quality Index; df: degree of freedom.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Silva et al (2011) and Araújo et al (2017) verified that substrates with organic constituents contributed to increase the number of leaves in Hancornia speciosa and Schizolobium amazonicum seedlings, respectively. Unlike the results presented herein, Erlacher et al (2016) found that the number of leaves of Eruca vesicaria and Brassica oleracea was higher with the use of ground assai pit, if compared to commercial substrate. According to Lima et al (2008), seedlings with a higher leaf production at the time of being taken to the field present a faster initial 1 SH: shoot height (cm); SD: stem diameter (mm); NL: number of leaves; SDM: shoot dry mass (g); RDM: root dry mass (g); TDM: total dry mass (g); DQI: Dickson Quality Index; df: degree of freedom.…”
Section: Resultscontrasting
confidence: 99%
“…Among the various residues from the Amazonian agro-industries, Brazil nut shell, acerola pit (Muniz 2017), assai pit (Erlacher et al 2016) and cupuassu peel (Dias 2012) stand out for presenting a high availability in the region and a physicochemical potential to formulate seedling production substrates (Soares et al 2014). Thus, this study aimed to evaluate the use of some agro-industrial residues as potential substrates for producing E. precatoria seedlings, in order to replace commercial products.…”
Section: Abstract Resumomentioning
confidence: 99%
“…Podemos observar na Tabela 3 que os dois compostos apresentaram maiores teores de macro e micronutrientes do que apresentado por Erlacher et al (2017) [8], que avaliou o uso de caroço de açaí para formulação de substratos na produção de mudas de hortaliças. Resultados expressivos também foram apontados por Maranho e Paiva (2012) [17], trabalhando na produção de mudas de pau de rosa (Physocalymma scaberrimum) quando obtiveram maiores alturas de mudas produzidas com substrato a partir de 100% de composto com resíduos orgânico da despolpa de açaí, até a formulação de 50% de resíduo, misturado a 50% de terra de mata.…”
Section: Resultsunclassified
“…Com a crescente produção de resíduos agroindustriais do beneficiamento do açaí, da pecuária e das madeireiras, há a preocupação com a contaminação do meio ambiente, devido o descarte incorreto [8]. Assim, há a necessidade de alternativas para o uso desses resíduos, dentre essas, se vislumbra o uso desses na agricultura [9], sendo um dos destinos a formulação de compostagem e/ou húmus para composição de substrato na produção de mudas, minimizando assim o risco de contaminação do meio ambiente.…”
Section: Introductionunclassified
“…Seguindo os princípios da política nacional dos resíduos sólidos, Elacher et al (2014) enfatiza o aproveitamento do caroço de açaí como adubo orgânico na agricultura, tornando-se uma alternativa mais utilizada para a destinação deste material, garantindo menos impactos ambientais e uma agricultura sustentável. Lisboa et al (2019) afirmam que através da pesquisa de revisão, reforça-se a evidenciação de técnicas para o correto descarte deste resíduo, apontando áreas de reaproveitamento como na compostagem, construção civil, saúde e alimentos.…”
Section: Fundamentação Teóricaunclassified